Analisis Strategi Penerjemahan Idiomatik Dalam Novel “ARTEMIS” Karya Andy Weir - Amalia, Ikeu Nur; Dewi, Ika Sari (JURNAL PENDIDIKAN & PENGAJARAN (JUPE2), 2024)
Idioms are one of the most commonly used figurative expressions in literary works, and they are often referred to as a problem that machine translators can never solve. This study aims to discover the strategies used in translating idioms in the novel "Artemis" by Andy Weir. This research uses a descriptive qualitative method. The data sources are idioms found in the book "Artemis" by Andy Weir. The results show that there are several translation strategies used in translating idioms in the novel "Artemis", namely Paraphrase, Similar Meaning and Form, Similar Meaning but Dissimilar Form, Omission of a Play on Idiom, Omission of the Entire Idiom, and Borrowing SL Idiom. Paraphrase is the most widely used idiom translation strategy, which is 30% of the total 74 data analyzed, and the least strategy is borrowing at 2% with only 6 data out of all the data analyzed. The findings in this study show that translators mostly apply the paraphrasing translation strategy because finding the same idiom in the target language is very difficult, so a paraphrasing strategy is needed so that the meaning contained in the source language can be conveyed well in the target language.